Perancangan Antarmuka Pengguna Portal Pencarian Kerja FirstJob.id Berbasis Web dengan pendekatan Human Centered Design - Faris Genis Yudi Perdana; Hanifah Muslimah Az-Zahra; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
There are many job search sites recently and yet still lack useful features on showing the available job list. This leads to the number of candidates which is apparently incompetence with the company wishes. Also, the fresh graduates often not much pay attention to the requirements or randomly apply for any jobs as possible without check their competences. Due to that, there is a trusted job search site which can solve that problem. the site's name is firstjob.id and developed by PT. Java Cipta Solusi. The idea is to make an interactive user interface job search site by using the Human Centered Design (HCD) approach, an approach to develop an interactive system for human. The design will be evaluated by using usability testing to know how easy it will be made when the site is used by the user and Focus Group Discussion (FGD) for knowing the user's need and expectation at firstjob.id. Then, the result needs to be evaluated again and finally, the user interface design will be easily used as the user's needs and expectation.